A case report of a rare strangulated incisional umbilical Richter’s hernia of the transverse colon - Sykes, Blake A.; Kapadia, Chitrakanti R. (International Surgery Journal, 2023)
Richter’s hernias are not uncommon, however there have been very few articles which describe this type of hernia of the transverse colon. This case report is regarding a 76-year-old gentleman who presented with periumbilical pain and obstipation and was found to have a Richter’s hernia of the anti-mesenteric transverse colon. He underwent an open extended right hemicolectomy to resect the strangulated contents of the hernia and made good recovery subsequently. Upon review of the literature, it is clear that this is a very rare content for a Richter’s hernia and we believe this is the second report of an incisional Richter’s hernia of this kind. This case report and the discussion of the literature reminds us of the pathology of a Richter’s hernia and the principles of its investigation and management.